High-frequency high-performance iron-nickel alloy magnetic powder core and preparation method and application thereof

By using the physical gas phase condensation method, and using ball mill blending and double-layer organic insulation coating technology, the existing metal magnetic powder core lacks performance during high-frequency applications is solved, and the high permeability, stability and quality factor is improved, while simplifying the process flow.

CN119601337AActive Publication Date: 2025-03-11CHINA IRON & STEEL RESEARCH INSTITUTE GROUP CO LTD

Patent Information

Application Number
CN202411682490.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-22
Publication Date
2025-03-11
Estimated Expiration
2044-11-22

AI Technical Summary

Technical Problem

It is difficult to take into account high permeability, permeability stability and high quality factors in high frequency applications, and the preparation process is complex.

Method used

The iron-nickel alloy powder prepared by selecting the physical vapor phase condensation method and blending it with nano SiO2 powder by ball-mill blending, combining with the double-layer organic insulating coating technology, including silicone resin and epoxy resin, as well as rare earth-doped nanoferrit powder and nanoAl2O3 powder, inorganic + double-layer organic insulating coating is achieved.

Benefits of technology

The permeability, permeability stability and quality factor are significantly improved, especially in high-frequency applications, and the preparation process is simplified and the cost is reduced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119601337A_ABST
    Figure CN119601337A_ABST
Patent Text Reader

Abstract

The invention relates to a high-frequency and high-performance iron-nickel alloy magnetic powder core and a preparation method and application thereof, belongs to the field of metal magnetic powder cores, and solves the problems that in the prior art, when a metal magnetic powder core is applied at high frequency, high magnetic conductivity, high magnetic conductivity stability and high quality factor are difficult to consider, and the saturation flux density is low. And the preparation process is tedious. The invention discloses a preparation method of a high-frequency high-performance iron-nickel alloy magnetic powder core. The preparation method comprises the following steps: S1, preparing raw materials; s2, performing pretreatment; s3, the pretreated iron-nickel alloy powder and nano SiO2 powder are blended, and inorganic insulation coating powder is obtained; s4, adding the inorganic insulating coating powder into a first coating agent to obtain inorganic and first organic insulating coating powder; s5, adding the inorganic and first organic insulation coating powder into a second coating agent to obtain inorganic and double-layer organic insulation coating powder; and S6, compression molding. The comprehensive magnetic performance of the iron-nickel magnetic powder core is improved, and the preparation process is simplified.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of metal magnetic powder core materials, and in particular to a high-frequency and high-performance iron-nickel alloy magnetic powder core and a preparation method and application thereof. Background Art

[0002] With the development of high-precision electronic technology, inductor components are also developing towards miniaturization and high frequency. The research and development of new magnetic powder core materials with high magnetic permeability and high quality factor at high operating frequency is the key to the development of new high-performance inductor components.

[0003] The operating frequency of traditional nickel-zinc ferrite powder cores is difficult to further increase due to the Snoek's limit. The operating frequency of metal powder core materials such as iron silicon aluminum, iron silicon molybdenum, and iron nickel sold on the market can only reach a few hundred kilohertz, which is relatively low and cannot meet the high-frequency requirements of devices. Carbonyl iron powder cores have high Q values ​​and low temperature permeability coefficients, but their permeability at high frequencies is low or their anti-saturation ability is poor, which is not conducive to improving their power density and also has serious aging phenomena. Iron-nickel powder cores, also known as high-flux powder cores, can meet the needs of miniaturization of inductor components. However, the existing iron-nickel powder cores are difficult to apply above 10MHz due to their low quality factor Q or low permeability at high frequencies.

[0004] In order to meet the high power density and high frequency application requirements of inductive components in the MHz frequency band, it is urgent to develop a metal magnetic powder core with excellent comprehensive performance at high frequencies. Summary of the invention

[0005] In view of the above analysis, the present invention aims to provide a high-frequency, high-performance iron-nickel alloy magnetic powder core and its preparation method and application, so as to solve at least one of the following problems existing in the prior art metal magnetic powder core in high-frequency applications: (1) it is difficult to take into account high magnetic permeability, high magnetic permeability stability, and high quality factor; (2) the saturation magnetic induction intensity is low; (3) the preparation process is cumbersome.

[0006] The objective of the present invention is achieved through the following technical solutions:

[0007] The present invention provides a method for preparing a high-frequency and high-performance iron-nickel alloy magnetic powder core, comprising the following steps:

[0008] S1. Raw material preparation:

[0009] An iron-nickel alloy powder obtained by a physical vapor condensation method is selected, wherein the average particle size D is less than 2 μm and [Fe] / [Ni] is 0.8-1.2; wherein [Fe] and [Ni] represent the mass percentages of Fe and Ni in the chemical composition of the iron-nickel alloy powder;

[0010] S2. Preprocessing:

[0011] The iron-nickel alloy powder is subjected to high temperature pretreatment in an oxygen-free environment;

[0012] S3, blending the pretreated iron-nickel alloy powder with nano-SiO2 powder by ball milling to obtain inorganic insulating coated powder;

[0013] S4, mixing an organic silicone resin, an epoxy resin, a coupling agent and a diluent to obtain a mixed resin; the mass ratio of the organic silicone resin to the epoxy resin is (1-5):1, and the diluent is a volatile solvent;

[0014] A portion of the mixed resin is taken out as the first resin, and the rare earth-doped nano ferrite powder is added to the first resin to obtain a first coating agent; the inorganic insulating coating powder obtained in S3 is added to the first coating agent, and stirred until the diluent in the first coating agent is completely volatilized to obtain an inorganic + first organic insulating coating powder;

[0015] S5, taking the remaining part of the mixed resin as the second resin, adding the nano-Al2O3 powder into the second resin to obtain a second coating agent; adding the inorganic + first organic insulating coating powder obtained in S4 into the second coating agent, stirring until the diluent in the second coating agent is completely volatilized, to obtain an inorganic + double-layer organic insulating coating powder;

[0016] S6. Pressing and molding: Pressing and molding the inorganic + double-layer organic insulating coating powder obtained in S5 to obtain an iron-nickel alloy magnetic powder core.

[0017] Furthermore, based on the mass of the iron-nickel alloy powder, in step S4, the total amount of the silicone resin and the epoxy resin added is 1-8wt%, and the amount of the coupling agent added is 0.5-3wt%.

[0018] Further, in step S5, nano-Al2O3 powder and layered MoS2, or layered MoS2 is added to a second resin to obtain a second coating agent; the lateral size of the layered MoS2 flakes is 10-30 μm.

[0019] Furthermore, based on the mass of the iron-nickel alloy powder, in step S3, the amount of nano-SiO2 powder added is 2-6wt%; and / or, in step S4, the amount of rare earth-doped nano-ferrite powder added is 0.5-2wt%; and / or, in step S5, the amount of nano-Al2O3 powder added is 0.5-2wt%.

[0020] Further, in step S4, the mass ratio of the silicone resin to the epoxy resin is (1.5-2.5):1; and / or,

[0021] In step S3, the particle size of the nano-SiO2 powder is 20-70nm; and / or, in step S4, the particle size of the rare earth-doped nano-ferrite powder is 5-50nm; and / or, in step S5, the particle size of the nano-Al2O3 powder is 5-70nm.

[0022] Further, in step S1, the coefficient of variation of the particle size distribution of the iron-nickel alloy powder, i.e., the CV value, is ≤ 25%; and / or,

[0023] The iron-nickel alloy powder is spherical particles, and the sphericity δ of each spherical particle is ≥ 99.6%; and / or,

[0024] The repose angle of the iron-nickel alloy powder is less than 30°.

[0025] Further, in step S4, the ferrite powder includes at least one of manganese-zinc ferrite powder, nickel-zinc ferrite powder, cobalt-zinc ferrite powder, nickel-copper-zinc ferrite powder, and manganese ferrite powder.

[0026] Further, in step S6, the pressure of the pressing molding is 700-900 MPa.

[0027] The present invention also provides an iron-nickel alloy magnetic powder core obtained by the preparation method as described above.

[0028] The present invention also provides an application of the above-mentioned iron-nickel alloy magnetic powder core in power electronics and magnetic elements operating in a frequency range of 30 MHz to 100 MHz.

[0029] Compared with the prior art, the present invention can achieve at least one of the following beneficial effects:

[0030] (1) The present invention endows the iron-nickel based magnetic powder core material with excellent comprehensive properties through multi-layer insulation coating, for example, significantly improving the magnetic permeability, magnetic permeability stability and quality factor, especially in high-frequency applications. Specifically, the present invention selects suitable iron-nickel alloy powder and nano-SiO2 powder, and adopts a simple and easy-to-operate ball milling blending method to uniformly coat the nano-SiO2 powder on the surface of the iron-nickel alloy powder particles. This coating can effectively isolate the direct contact between the metal particles and reduce the eddy current loss, thereby helping to improve the magnetic permeability, quality factor and obtain a more stable magnetic permeability change rate. Compared with a single-layer organic insulating coating or the use of an organic resin alone or simply using an organic resin for organic coating, the present invention adopts a double-layer organic insulating coating, and each layer of the organic insulating coating includes two resins (silicone resin and epoxy resin) and an inorganic powder. By controlling the appropriate ratio of the silicone resin and the epoxy resin, the synergistic effect of the two is utilized to improve the magnetic permeability, magnetic permeability stability and quality factor of the magnetic powder core, while also achieving improvements in its mechanical strength and environmental adaptability; at the same time, the inorganic powders in the double-layer coating, such as rare earth-doped nano ferrite powder and Al2O3 powder, are also beneficial to improving the magnetic permeability, magnetic permeability stability and quality factor of the magnetic powder core.

[0031] (2) Compared with simply using organic resin for organic insulation coating, the present invention can not only reduce magnetic loss to improve magnetic permeability and quality factor, but also improve saturation magnetic induction intensity, thereby improving the comprehensive magnetic properties of the magnetic powder core by adding rare earth-doped nano ferrite powder to the organic insulation coating layer.

[0032] (3) Compared with the methods of achieving inorganic insulation coating in the prior art (chemical reaction coating, sol-gel method, chemical vapor method, chemical co-precipitation method, etc.), the present invention is based on suitable iron-nickel alloy powder and nano-SiO2 powder, and can achieve effective inorganic insulation coating through ball milling blending, which not only simplifies the process flow and reduces costs, but also improves the performance of the magnetic powder core, which is conducive to large-scale application.

[0033] (4) In some preferred embodiments, by controlling the particle size and addition amount of SiO2 powder, controlling the particle size and addition amount of rare earth-doped ferrite powder, controlling the particle size and addition amount of Al2O3 powder, and adding layered MoS2 in the second organic insulating coating, it is beneficial to further improve the comprehensive magnetic properties of the magnetic powder core. By controlling the addition amount of the coating agent and the ratio of the silicone resin and the epoxy resin, it is beneficial to achieve excellent magnetic properties while ensuring good mechanical properties and thermal stability, especially in the high frequency range.

[0034] In the present invention, the above-mentioned technical solutions can also be combined with each other to achieve more preferred combination solutions. Other features and advantages of the present invention will be described in the subsequent description, and some advantages can become obvious from the description, or can be understood by practicing the present invention. The purpose and other advantages of the present invention can be realized and obtained through the contents particularly pointed out in the description and the drawings. BRIEF DESCRIPTION OF THE DRAWINGS

[0035] The drawings are only for the purpose of illustrating particular embodiments and are not to be considered limiting of the present invention. Like reference symbols denote like components throughout the drawings.

[0036] Figure 1 SEM photos of iron-nickel alloy powder selected for the embodiment of the present invention; wherein a is a SEM photo of an iron-nickel alloy powder with an average particle size of 0.8 μm, and b is a SEM photo of an iron-nickel alloy powder with an average particle size of 1.3 μm;

[0037] Figure 2 The particle size distribution diagram of the iron-nickel alloy powder selected for the embodiment of the present invention, wherein (a) is a particle size distribution diagram of an average particle size of 0.8 μm, and (b) is a particle size distribution diagram of an average particle size of 1.3 μm;

[0038] Figure 3 This is a SEM photo of the iron-nickel alloy powder selected for Comparative Example 1;

[0039] Figure 4 The magnetic permeability curves of the magnetic powder cores prepared in Examples 1 and 2 and Comparative Example 1 of the present invention vary with frequency;

[0040] Figure 5 The quality factor of the magnetic powder cores prepared in Examples 1 and 2 and Comparative Example 1 of the present invention varies with frequency;

[0041] Figure 6 The magnetic permeability curves of the magnetic powder cores prepared in Examples 1, 7-10 of the present invention vary with frequency;

[0042] Figure 7 The curves showing the change of quality factor with frequency for the magnetic powder cores prepared in Examples 1, 7-10 of the present invention. DETAILED DESCRIPTION

[0043] The preferred embodiments of the present invention are described in detail below in conjunction with the accompanying drawings, wherein the accompanying drawings constitute a part of this application and are used together with the embodiments of the present invention to illustrate the principles of the present invention, but are not used to limit the scope of the present invention.

[0044] Iron-nickel alloy powder is a key material for manufacturing high-performance magnetic powder cores. Its powder particle size and distribution, surface morphology, chemical composition, powder morphology and other characteristics have an important impact on the performance of the final magnetic powder core product. Existing methods for preparing iron-nickel alloy powder mainly include atomization, reduction-diffusion and mechanical alloying. However, after detailed analysis, the inventors of the present invention found that compared with these traditional methods, iron-nickel alloy powder prepared by physical vapor condensation (PVD) is more suitable for the preparation of magnetic powder cores. Despite this, most of the iron-nickel alloy powder raw materials currently used for the preparation of magnetic powder cores on the market are still prepared by atomization, reduction-diffusion and mechanical alloying, and rarely involve powders prepared by PVD. Therefore, how to determine the iron-nickel alloy powder suitable for solving the technical problem that the comprehensive performance of the metal magnetic powder core of the present invention is not ideal when used in high-frequency applications from the many categories prepared by the PVD method, there is currently a lack of relevant technical reports.

[0045] In addition to the selection of raw materials, the selection of coating agents and coating methods used for the insulation coating of iron-nickel alloy powders also directly affect the performance of the final product. At present, the coating process of iron-nickel alloy powders is mostly complicated, especially the inorganic coating process, and the comprehensive performance of the coated iron-nickel alloy powders at high frequencies, including magnetic permeability, quality factor, saturation magnetic induction intensity, and magnetic loss, often has some deficiencies, making it difficult to fully meet the application requirements under high-frequency and high-power conditions.

[0046] Based on this, in the first aspect, the present invention provides a method for preparing a high-frequency and high-performance iron-nickel alloy magnetic powder core, comprising the following steps:

[0047] S1. Raw material preparation:

[0048] An iron-nickel alloy powder obtained by a physical vapor condensation method is selected, wherein the average particle size D is less than 2 μm and [Fe] / [Ni] is 0.8-1.2; wherein [Fe] and [Ni] represent the mass percentages of Fe and Ni in the chemical composition of the iron-nickel alloy powder;

[0049] S2. Preprocessing:

[0050] The iron-nickel alloy powder is subjected to high temperature pretreatment in an oxygen-free environment;

[0051] S3, blending the pretreated iron-nickel alloy powder with nano-SiO2 powder by ball milling to obtain inorganic insulating coated powder;

[0052] S4, mixing an organic silicone resin, an epoxy resin, a coupling agent and a diluent to obtain a mixed resin; the mass ratio of the organic silicone resin to the epoxy resin is (1-5):1, and the diluent is a volatile solvent;

[0053] A portion of the mixed resin is taken out as the first resin, and the rare earth-doped nano ferrite powder is added to the first resin to obtain a first coating agent; the inorganic insulating coating powder obtained in S3 is added to the first coating agent, and stirred until the diluent in the first coating agent is completely volatilized to obtain an inorganic + first organic insulating coating powder;

[0054] S5, taking the remaining part of the mixed resin as the second resin, adding the nano-Al2O3 powder into the second resin to obtain a second coating agent; adding the inorganic + first organic insulating coating powder obtained in S4 into the second coating agent, stirring until the diluent in the second coating agent is completely volatilized, to obtain an inorganic + double-layer organic insulating coating powder;

[0055] S6. Pressing and molding: Pressing and molding the inorganic + double-layer organic insulating coating powder obtained in S5 to obtain an iron-nickel alloy magnetic powder core.

[0056] Compared with the prior art, the present invention endows the iron-nickel based magnetic powder core material with excellent comprehensive performance through multi-layer insulation coating, for example, significantly improving the magnetic permeability, magnetic permeability stability and quality factor, especially in high-frequency applications. Specifically, the present invention selects suitable iron-nickel alloy powder and nano-SiO2 powder, adopts a simple and easy-to-operate ball milling blending method, and makes the nano-SiO2 powder uniformly coated on the surface of the iron-nickel alloy powder particles. This coating can effectively isolate the direct contact between the metal particles and reduce the eddy current loss, thereby helping to improve the magnetic permeability, quality factor and obtain a more stable magnetic permeability change rate. Compared with a single-layer organic insulating coating or the use of an organic resin alone or simply using an organic resin for organic coating, the present invention adopts a double-layer organic insulating coating, and each layer of the organic insulating coating includes two resins (silicone resin and epoxy resin) and an inorganic powder. By controlling the appropriate ratio of the silicone resin and the epoxy resin, the synergistic effect of the two is utilized to improve the magnetic permeability, magnetic permeability stability and quality factor of the magnetic powder core, while also achieving improvements in its mechanical strength and environmental adaptability; at the same time, the inorganic powders in the double-layer coating, such as rare earth-doped nano ferrite powder and Al2O3 powder, are also beneficial to improving the magnetic permeability, magnetic permeability stability and quality factor of the magnetic powder core.

[0057] Compared with simply using organic resin for organic insulation coating, the present invention can not only reduce magnetic loss to improve magnetic permeability and quality factor, but also improve saturation magnetic induction intensity, thereby improving the comprehensive magnetic properties of the magnetic powder core by adding rare earth-doped nano ferrite powder to the organic insulation coating layer.

[0058] Compared with the methods of achieving inorganic insulation coating in the prior art (chemical reaction coating, sol-gel method, chemical vapor method, chemical co-precipitation method, etc.), the present invention is based on suitable iron-nickel alloy powder and nano-SiO2 powder, and can achieve effective inorganic insulation coating through ball milling blending, which not only simplifies the process flow and reduces costs, but also improves the performance of the magnetic powder core, which is conducive to large-scale application.

[0059] It can be seen that the present invention effectively improves the comprehensive magnetic properties of the iron-nickel based magnetic powder core and simplifies the preparation process through material selection and multi-layer insulation coating.

[0060] Exemplarily, the diluent includes one or a mixture of acetone, ethanol, methanol, toluene.

[0061] In some preferred embodiments, based on the mass of the iron-nickel alloy powder, in step S4, the total amount of the silicone resin and the epoxy resin added is 1-8wt%, and the amount of the coupling agent added is 0.5-3wt%. By controlling the amount of the resin and the coupling agent added within a suitable range, the optimized balance of the magnetic properties, mechanical strength and thermal stability of the magnetic powder core can be ensured. If the amount of the resin and / or the coupling agent added is too high, the iron-nickel alloy powder will be over-coated, affecting its magnetic properties, such as causing the magnetic permeability and saturation magnetic induction intensity to decrease, and the mechanical strength and hardness and thermal stability of the magnetic powder core will also be reduced, thereby affecting its durability in practical applications. If the amount of the resin and / or the coupling agent added is too low, the expected modification effect cannot be achieved, such as being unfavorable for improving mechanical properties and heat resistance, or the purpose of reducing magnetic loss, improving magnetic permeability and quality factor cannot be achieved.

[0062] Exemplarily, the total amount of the silicone resin and the epoxy resin added is 2wt%, 3wt%, 4wt%, 5wt%, 6wt%, 7wt%, and the amount of the coupling agent added is 1.0wt%, 1.5wt%, 2.0wt%, 2.5wt%.

[0063] In some preferred embodiments, in step S5, nano Al2O3 powder and layered MoS2, or layered MoS2 is added to the second resin to obtain a second coating agent; the lateral dimension of the layered MoS2 powder is 10-30 μm. Preferably, based on the mass of the iron-nickel alloy powder, the total amount of the nano Al2O3 powder and / or layered MoS2 added is ≤3wt%. The addition of layered MoS2 and controlling the total amount of inorganic substances added in the second organic insulating coating within a suitable range are conducive to further improving the magnetic permeability and quality factor of the magnetic powder core, especially at high frequencies.

[0064] In some preferred embodiments, in step S3, the addition amount of the nano-SiO2 powder is 2-6wt% based on the mass of the iron-nickel alloy powder. By controlling the addition amount of the nano-SiO2 powder within a suitable range, the quality factor and magnetic permeability under high frequency can be better balanced. Too much addition of the nano-SiO2 powder is not conducive to improving the magnetic permeability under high frequency, because too much SiO2 insulating material will increase the content of non-magnetic substances in the magnetic powder core, thereby reducing the effective magnetic permeability; too little addition of the nano-SiO2 powder is not conducive to improving the quality factor under high frequency, because nano-SiO2 plays an important role in improving resistivity and reducing core loss, and insufficient addition will not be able to give full play to its insulation and performance improvement effects.

[0065] Exemplarily, the addition amount of nano-SiO2 powder is 2.5wt%, 3.5wt%, 4.5wt%, 5.5wt%.

[0066] In some preferred embodiments, in step S4, based on the mass of the iron-nickel alloy powder, the amount of the rare earth-doped nano ferrite powder added is 0.5-2wt%; and / or, in step S5, the amount of the nano Al2O3 powder added is 0.5-2wt%; and / or, the amount of the layered MoS2 powder added is 0.5-2wt%. By reasonably controlling these proportions, the advantages of rare earth-doped nano ferrite powder and nano Al2O3 powder in improving the comprehensive magnetic properties of the magnetic powder core, enhancing mechanical strength and improving thermal stability can be fully utilized, and the best balance between performance and cost of the magnetic powder core can be achieved. Too much rare earth-doped nano ferrite powder or Al2O3 powder will affect the magnetic coupling between the magnetic powder particles, resulting in an increase in magnetic loss and a decrease in magnetic permeability; too little addition will not effectively exert the effect of rare earth-doped nano ferrite powder or Al2O3 powder on performance improvement.

[0067] Exemplarily, the addition amount of rare earth doped nano ferrite powder, Al2O3 powder or layered MoS2 powder is 0.8wt%, 1.0wt%, 1.2wt%, 1.5wt%, 1.8wt%.

[0068] Preferably, in step S4, the mass ratio of the silicone resin to the epoxy resin is (1.5-2.5):1. By precisely controlling the ratio of the two resins, it is more conducive to the magnetic powder core to achieve an optimal balance between excellent magnetic properties, mechanical properties and thermal stability. Exemplarily, the ratio of silicone resin to epoxy resin is 1.7:1, 2:1, 2.2:1.

[0069] In some embodiments, in step S3, the particle size of the nano-SiO2 powder is 20-70 nm; and / or, in step S4, the particle size of the rare earth-doped nano-ferrite powder is 5-50 nm; and / or, in step S5, the particle size of the nano-Al2O3 powder is 5-70 nm. Exemplarily, the rare earth-doped nano-ferrite powder is spinel ferrite powder.

[0070] Exemplarily, the particle size of the nano-SiO2 is 30nm, 40nm, 50nm, or 60nm.

[0071] Exemplarily, the particle size of the rare earth doped nano ferrite powder is 10 nm, 15 nm, 20 nm, 30 nm, 40 nm. The particle size of the nano Al2O3 powder is 10 nm, 20 nm, 30 nm, 40 nm, 50 nm, 60 nm.

[0072] Preferably, the particle size of the nano-SiO2 powder is 20-40 nm.

[0073] Preferably, the particle size of the rare earth doped nano ferrite powder is 5-20 nm.

[0074] Preferably, the particle size of the nano-Al2O3 powder is 5-50nm.

[0075] Optionally, the ferrite powder includes at least one of manganese-zinc ferrite powder, nickel-zinc ferrite powder, cobalt-zinc ferrite powder, nickel-copper-zinc ferrite powder, and manganese ferrite powder.

[0076] In some preferred embodiments, the molecular formula of the rare earth doped ferrite powder is Ni 0.5 Zn 0.5 RE x Fe 2- x O4、Mn 0.5 Zn 0.5 RE x Fe 2-x O4、Co 0.5 Zn 0.5 RE x Fe 2-x O4, wherein RE is a rare earth element, including but not limited to at least one of La, Ce, Tb, Nd, Eu, Sm, Gd, Sc, Dy, Yb, Ho, Er, Tm, Lu, and Y; x = 0.02, 0.03, 0.04, 0.05, 0.06, 0.07, 0.08, and 0.09.

[0077] In one embodiment, the Ni 0.5 Zn 0.5 RE x Fe2-x The preparation method of O4 comprises: 0.5 Zn 0.5 RE x Fe 2-x The chemical composition of O4, nickel chloride (Xmol / L), zinc chloride (Xmol / L), ferric chloride hexahydrate (Xmol / L) and rare earth chloride (0.1×Xmol / L) salt solution are measured in stoichiometric ratio, 50-150mL deionized water is added for dilution and mixing. The mixed homogeneous solution is placed in a constant temperature water bath, heated to 75-85°C and stirred, NaOH is added dropwise, pH=10-11 is adjusted, and stirring is continued for 2-4 hours to promote the reaction and generate a brown precipitate. The precipitate is washed with deionized water until the pH drops to 7. The precipitate is separated by vacuum filtration, dried at 80-90°C for 16-32 hours, taken out, and ground into powder to obtain rare earth-doped nickel-zinc ferrite powder. Exemplarily, X=2-5mol / L; for example, X=3mol / L, 4mol / L.

[0078] Exemplarily, 120 mL of deionized water is added, the mixed homogeneous solution is placed in a constant temperature water bath, heated to 82° C. and stirred, NaOH is added dropwise to adjust the pH to 10-11, and stirring is continued for 3 hours; the precipitate is separated by vacuum filtration and dried at 87° C. for 18 hours.

[0079] In some embodiments, the Mn 0.5 Zn 0.5 RE x Fe 2-x O4 or Co 0.5 Zn 0.5 RE x Fe 2-x Preparation method of O4 and Ni 0.5 Zn 0.5 RE x Fe 2-x O4 is similar, except that nickel chloride is replaced by water and manganese chloride, water and cobalt chloride, such as manganese chloride tetrahydrate or cobalt chloride hexahydrate.

[0080] In some embodiments, in step S1, the coefficient of variation of the particle size distribution of the iron-nickel alloy powder, i.e., the CV value, is ≤25%, more preferably below 20%, and further preferably below 15%, which indicates that the particle size distribution of the iron-nickel alloy powder is narrow.

[0081] In some embodiments, in step S1, the particle size of the iron-nickel alloy powder further satisfies: max -D min ≤2.4μm; more preferably D max -D min ≤1.8μm; Dmax is the maximum particle size, D min The minimum particle size.

[0082] In some embodiments, in step S1, the iron-nickel alloy powder is spherical particles, and the sphericity δ of each spherical particle is ≥ 99.6%, which indicates that the iron-nickel alloy powder particles have high sphericity.

[0083] In some embodiments, in step S1, the angle of repose of the iron-nickel alloy powder is less than 30°, which indicates that the iron-nickel alloy powders are not adhered to each other and have good fluidity. Exemplarily, the angle of repose is 25°.

[0084] In some embodiments, in step S1, the surface roughness of the iron-nickel alloy powder is Ra≤100nm. Preferably, Ra≤50nm.

[0085] Iron-nickel alloy powders with small particle size, narrow distribution, no sticking, and good sphericity are preferred to further improve the magnetic properties of the magnetic powder core at high frequencies. Because the smaller the particle size of the iron-nickel alloy powder in the magnetic powder core and the more uniform the particle size, the lower the eddy current loss, thereby improving the magnetic permeability and quality factor of the magnetic powder core; the non-stickiness between powders is conducive to a more uniform mixing of insulating materials, coupling agents, and organic resins, ensuring that there are insulating materials between particles, thereby reducing losses, improving the magnetic permeability and quality factor of the magnetic powder core, and making it more suitable for high-frequency work; when the alloy powder has better sphericity and a smoother surface, the insulating material on the powder surface is not easily damaged under high pressure, ensuring insulation between powders, thereby improving the magnetic permeability and quality factor of the magnetic powder core at high frequencies and obtaining a more stable rate of change of magnetic permeability.

[0086] In some embodiments, the particle size distribution of the iron-nickel alloy powder includes:

[0087] Case (1): 85% or more of the Fe-Ni powder has a particle size of 0.3-1.2 μm; or

[0088] Case (2): 90% or more of the Fe-Ni powder has a particle size of 0.9-1.8 μm.

[0089] In some embodiments, in step S6, the pressure of the pressing molding is 700-900 MPa.

[0090] Exemplarily, the compression molding pressure is 750 MPa, 800 MPa, or 850 MPa.

[0091] In some embodiments, in step S1, the chemical composition of the iron-nickel alloy powder includes, by mass percentage: Fe: 49.5-50.4%, C≤0.05%, O≤0.35%, and the remainder is Ni and unavoidable impurities.

[0092] In some preferred embodiments, in step S1, [Fe] / [Ni] is 0.95-1.05, and illustratively, [Fe] / [Ni]=1:1.

[0093] In some embodiments, in the pretreatment step S2, the atmosphere of the oxygen-free environment includes one or more of hydrogen, argon, and nitrogen. The temperature of the high-temperature pretreatment is 400-650°C.

[0094] In some embodiments, in step S3, the parameters of the ball milling include: a ball-to-material mass ratio of 10:1 to 40:1; a rotation speed of 50 r / min-500 r / min, and a time of 0.5-8 h.

[0095] In some embodiments, in steps S4 and S5, the stirring is mechanical stirring under ultrasonic oscillation conditions, and the rotation speed of the mechanical stirring is 100-500 r / min.

[0096] Preferably, in step S4, the silicone resin includes at least one of methyl phenyl silicone resin, bisphenol A epoxy resin, polyimide-modified silicone resin, and acrylate-modified silicone resin.

[0097] Preferably, in step S4, the coupling agent includes at least one of vinyl triethoxy silane, vinyl trimethoxy silane, vinyl tri(β-methoxyethoxy) silane, γ-methacryloxypropyl trimethoxy silane, γ-aminopropyl triethoxy silane, and phosphate titanium coupling agent.

[0098] In some embodiments, in step S1, the iron-nickel alloy powder is prepared by a physical vapor condensation method, the main steps of which include:

[0099] (1) Add the iron-nickel alloy raw material with purity ≥99.9% into the high-temperature evaporator and evacuate to a vacuum degree of ≤10 -4 After 100 kPa, nitrogen is charged into the reaction system until the internal pressure is 100-200 kPa;

[0100] (2) Then, the plasma gun on the top of the high-temperature evaporator is turned on to make its power reach 60-100 kW to form iron-nickel alloy vapor, which is then transported to a particle controller connected to the high-temperature evaporator with a nitrogen gas flow at a flow rate of 2-5 m / s to collide and fuse;

[0101] (3) The particles after collision and fusion are transported to the bottom of the collector hopper along with nitrogen gas to obtain an iron-nickel alloy powder with a purity of ≥99% and an average particle size of <2 μm.

[0102] In some embodiments, the method for preparing the nano-SiO2 powder specifically comprises the following steps:

[0103] (1) Anhydrous ethanol, water and ammonia water are mixed in a ratio of (35-40):1:3, and ultrasonically vibrated for 10-30 minutes, which is recorded as liquid A; the concentration of ammonia water is 20%-30%; illustratively, the ratio of anhydrous ethanol, water and ammonia water is 37.5:1:3, and the concentration of ammonia water is 25%;

[0104] (2) dissolving 3-9 ml of hexyl orthosilicate in 40-60 ml of anhydrous ethanol, and ultrasonically shaking for 20-40 min, which is referred to as liquid B; illustratively, the volume of hexyl orthosilicate is 6 ml, and the volume of anhydrous ethanol is 50 ml;

[0105] (3) After stirring the A solution at a constant temperature of 30-70°C for 5-20 minutes, the B solution is slowly poured into the solution in 1-3 portions, and the solution is reacted for a certain period of time until the solution becomes turbid and then collected. The collected solution is filtered and washed to obtain a filter residue, and the filter residue is vacuum dried to obtain nano-SiO2 powder. For example, the B solution is slowly poured into the solution in 2 portions and vacuum dried at 100°C.

[0106] In a second aspect, the present invention further provides an iron-nickel alloy magnetic powder core obtained by the preparation method described in the first aspect.

[0107] In some embodiments, the iron-nickel alloy magnetic powder core has a magnetic permeability greater than 22 and a maximum quality factor greater than 240 at a high frequency of 30 MHz to 100 MHz, a frequency corresponding to the maximum quality factor greater than 32 MHz, and a quality factor greater than 39 at 100 MHz.

[0108] In some embodiments, the operating temperature range of the iron-nickel alloy magnetic powder core is -60°C to 200°C, and the density after pressing is ≥6.8g / cm 3 , saturation magnetic induction intensity Bs≥1.30T.

[0109] In a third aspect, the present invention further provides an application of the iron-nickel alloy powder core as described in the second aspect in power electronics and magnetic components operating in a frequency range of 30 MHz to 100 MHz.

[0110] The power electronics and magnetic components include but are not limited to: inductors, transformers, filters, and chokes.

[0111] The technical solution of the present invention is further described in detail below in conjunction with specific embodiments and comparative examples.

[0112] Embodiment 1:

[0113] This embodiment provides a method for preparing a high-frequency, high-performance iron-nickel alloy magnetic powder core, comprising the following steps:

[0114] S1. Raw material preparation:

[0115] The iron-nickel alloy powder obtained by physical vapor condensation method has an average particle size of D = 1.3 μm, chemical composition is shown in Table 1, and SEM photos are shown in Figure 1 (b) shows the particle size distribution. Figure 2 (b);

[0116] Table 1: Iron-nickel alloy composition table (average particle size D = 1.3 μm)

[0117] Element Fe Ni C O Mass percentage (wt%) 50.08 margin 0.032 0.277

[0118] S2. Preprocessing:

[0119] The iron-nickel alloy powder was subjected to high temperature pretreatment at 450°C for 1 hour in a H2 / Ar mixed gas environment with a volume ratio of 1:1;

[0120] S3, blending the high temperature pretreated iron-nickel alloy powder and SiO2 powder by ball milling to obtain an inorganic insulating coated powder; the average particle size of the SiO2 powder is 72nm and the addition amount is 1wt%;

[0121] S4, silicone resin Epoxy resin AFG-90H and coupling agent, namely vinyl triethoxysilane, are added to acetone and mixed to obtain a mixed resin; based on the mass of the iron-nickel alloy powder, the total amount of the silicone resin and the epoxy resin added is 8wt%, wherein the mass ratio of the silicone resin to the epoxy resin is 1:1, and the amount of the coupling agent added is 3wt%;

[0122] 1 / 2 (i.e., half) of the mixed resin is taken out as the first resin, and rare earth-doped ferrite powder is added to the first resin to obtain a first coating agent; wherein the rare earth-doped ferrite powder is manganese-zinc ferrite powder doped with the rare earth element Sm, and its chemical formula is Mn 0.5 Zn 0.5 RE x Fe 2-x O4, RE is Sm, x=0.02, its average particle size is 14.6nm and the addition amount is 2.0wt%; the inorganic insulating coating powder obtained from S3 is added to the first coating agent, and mechanically stirred at a speed of 300r / min under ultrasonic oscillation until the acetone is completely volatilized to obtain an inorganic + first organic insulating coating powder;

[0123] S5, taking the remaining 1 / 2 of the mixed resin as the second resin, adding nano-Al2O3 powder to the second resin to obtain a second coating agent; wherein the average particle size of the Al2O3 powder is 64nm and the addition amount is 2.0wt%; adding the inorganic + first organic insulating coating powder obtained in S4 to the second coating agent, and mechanically stirring at a speed of 300r / min under ultrasonic oscillation until the acetone is completely volatilized to obtain an inorganic + double-layer organic insulating coating powder;

[0124] S6. Pressing and molding: Pressing and molding the inorganic + double-layer organic insulating coating powder obtained in S5 at 700 MPa to obtain an iron-nickel alloy magnetic powder core.

[0125] Embodiment 2:

[0126] The difference between this embodiment and embodiment 1 is that in step S1, the average particle size of the iron-nickel alloy powder is 0.8 μm, the chemical composition is shown in Table 2, and the SEM photo is shown in Figure 1 (a) shows the particle size distribution. Figure 2 (a); in step S4, the total amount of the silicone resin and the epoxy resin added is 1wt%, the mass ratio of the silicone resin to the epoxy resin is 5:1, and the amount of the coupling agent added is 0.5wt%; the amount of the rare earth-doped manganese-zinc ferrite powder added is 0.5wt%, and in step S5, the amount of the Al2O3 powder added is 0.5wt%; the remaining steps and parameters are similar to those in Example 1.

[0127] Table 2: Iron-nickel alloy composition table (average particle size D = 0.8 μm)

[0128] Element Fe Ni C O Mass percentage (wt%) 50.21 margin 0.033 0.327

[0129] Embodiment 3:

[0130] The difference between this embodiment and embodiment 2 is that: in step S4, the total addition amount of the silicone resin and the epoxy resin is 3wt%, the mass ratio of the silicone resin to the epoxy resin is 1.5:1, and the addition amount of the coupling agent is 1.0wt%; the addition amount of the rare earth-doped manganese-zinc ferrite powder is 1.5wt%, and in step S5, the addition amount of the Al2O3 powder is 1.5wt%; the remaining steps and parameters are similar to those in embodiment 2.

[0131] Embodiment 4:

[0132] The difference between this embodiment and embodiment 2 is that: in step S4, the total addition amount of the silicone resin and the epoxy resin is 6wt%, the mass ratio of the silicone resin to the epoxy resin is 2.5:1, and the addition amount of the coupling agent is 1.5wt%; the addition amount of the rare earth-doped manganese-zinc ferrite powder is 1.25wt%, and in step S5, the addition amount of the Al2O3 powder is 1.25wt%; the remaining steps and parameters are similar to those in embodiment 2.

[0133] Embodiment 5:

[0134] The difference between this embodiment and embodiment 4 is that in step S4, the total addition amount of the silicone resin and the epoxy resin is 5wt%, the mass ratio of the silicone resin to the epoxy resin is 2:1, and the addition amount of the coupling agent is 2wt%; the remaining steps and parameters are similar to those of embodiment 4.

[0135] Embodiment 6:

[0136] The difference between this embodiment and embodiment 5 is that in step S3, the average particle size of the SiO2 powder is 30 nm; the remaining steps and parameters are similar to those of embodiment 5.

[0137] Embodiment 7:

[0138] The difference between this embodiment and embodiment 1 is that in step S3, the average particle size of the SiO2 powder is 30 nm and the addition amount is 2 wt%; the remaining steps and parameters are similar to those in embodiment 1.

[0139] Embodiment 8:

[0140] The difference between this embodiment and embodiment 1 is that in step S3, the average particle size of the SiO2 powder is 30 nm and the addition amount is 4 wt%; the remaining steps and parameters are similar to those in embodiment 1.

[0141] Embodiment 9:

[0142] The difference between this embodiment and embodiment 1 is that in step S3, the average particle size of the SiO2 powder is 30 nm and the addition amount is 6 wt%; the remaining steps and parameters are similar to those in embodiment 1.

[0143] Embodiment 10:

[0144] The difference between this embodiment and embodiment 1 is that in step S3, the average particle size of the SiO2 powder is 30 nm and the addition amount is 8 wt%; the remaining steps and parameters are similar to those in embodiment 1.

[0145] Embodiment 11

[0146] The difference between this embodiment and embodiment 6 is that in step S3, the amount of SiO2 powder added is 6wt%; in step S4, the rare earth doped ferrite powder is a nickel zinc ferrite powder doped with rare earth element Dy, and its chemical formula is Ni 0.5 Zn 0.5 RE x Fe 2-x O4, RE is Dy, x=0.05, the average particle size is 12.4 nm and the addition amount is 1.25 wt%; the remaining steps and parameters are similar to those of Example 6.

[0147] Example 12

[0148] The difference between this embodiment and embodiment 11 is that in step S4, the rare earth doped ferrite powder is a rare earth element Yb doped nickel zinc ferrite powder, and its chemical formula is Ni 0.5 Zn 0.5 RE x Fe 2-x O4, RE is Yb, x=0.02, and the average particle size is 10.9 nm; the remaining steps and parameters are similar to those of Example 11.

[0149] Embodiment 13

[0150] The difference between this embodiment and embodiment 11 is that in step S4, the rare earth doped ferrite powder is cobalt zinc ferrite powder doped with rare earth element Yb, and its chemical formula is Co 0.5 Zn 0.5 RE x Fe 2-x O4, RE is Yb, x=0.09, and the average particle size is 8.1 nm; the remaining steps and parameters are similar to those of Example 11.

[0151] Embodiment 14

[0152] The difference between this embodiment and Embodiment 13 is that in step S5, the average particle size of the Al2O3 powder is 30 nm; the remaining steps and parameters are similar to those of Embodiment 13.

[0153] Embodiment 15

[0154] The difference between this embodiment and embodiment 13 is that: in step S5, layered MoS2 is added to the second resin to obtain a second coating agent; the average lateral size of the layered MoS2 flakes is 15 μm and the addition amount is 1.25 wt%; the remaining steps and parameters are similar to those of embodiment 13.

[0155] Comparative Example 1

[0156] The difference between this comparative example and Example 1 is that in step S1, the average particle size D of the iron-nickel alloy powder is 3.2 μm, and the SEM photo is as follows: Figure 3 As shown; the remaining steps and parameters are similar to those in Example 1.

[0157] Comparative Example 2

[0158] The difference between this comparative example and Example 1 is that in step S4, the mass ratio of the silicone resin to the epoxy resin is 0.5:1; the remaining steps and parameters are similar to those in Example 1.

[0159] Comparative Example 3

[0160] The difference between this comparative example and Example 1 is that in step S4, the mass ratio of the silicone resin to the epoxy resin is 7:1; the remaining steps and parameters are similar to those of Example 1.

[0161] Comparative Example 4

[0162] The difference between this comparative example and Example 1 is that in step S4: 1 / 2 of the mixed resin is taken out directly as the first coating agent (ie, the first coating agent does not contain ferrite powder); the remaining steps and parameters are similar to those of Example 1.

[0163] Comparative Example 5

[0164] The difference between this comparative example and Example 1 is that in step S5: the remaining 1 / 2 of the mixed resin is directly used as the second coating agent (that is, the second coating agent does not contain Al2O3 powder); the remaining steps and parameters are similar to those of Example 1.

[0165] Comparative Example 6

[0166] The difference between this comparative example and Example 1 is that there is no step S3; in step S4, the iron-nickel alloy powder after high-temperature pretreatment is directly added to the first coating agent (ie, without SiO2 insulating coating); the remaining steps and parameters are similar to those of Example 1.

[0167] Comparative Example 7

[0168] The difference between this comparative example and Example 1 is that S4, the silicone resin Epoxy resin AFG-90H and coupling agent, namely vinyl triethoxysilane, are added to acetone and mixed to obtain a mixed resin; based on the mass of the iron-nickel alloy powder, the total amount of the silicone resin and the epoxy resin added is 4wt%, wherein the mass ratio of the silicone resin to the epoxy resin is 1:1, and the amount of the coupling agent added is 1.5wt%;

[0169] S5. Add nano Al2O3 powder to the mixed resin to obtain a coating agent; wherein the average particle size of the Al2O3 powder is 64nm and the addition amount is 2.0wt%; add the inorganic insulating coating powder obtained in S3 to the coating agent, and mechanically stir at a speed of 300r / min under ultrasonic oscillation until the acetone is completely volatilized to obtain an inorganic + single-layer organic insulating coating powder; the remaining steps and parameters are similar to those in Example 1.

[0170] Comparative Example 8

[0171] The difference between this comparative example and Example 1 is that S4, the silicone resin Epoxy resin AFG-90H and coupling agent, namely vinyl triethoxysilane, are added to acetone and mixed to obtain a mixed resin; based on the mass of the iron-nickel alloy powder, the total amount of the silicone resin and the epoxy resin added is 4wt%, wherein the mass ratio of the silicone resin to the epoxy resin is 1:1, and the amount of the coupling agent added is 1.5wt%;

[0172] Manganese zinc ferrite powder is added to the mixed resin to obtain a coating agent; wherein the average particle size of the manganese zinc ferrite powder is 20 nm and the addition amount is 2.0 wt%; the inorganic insulating coating powder obtained in S3 is added to the coating agent, and mechanical stirring is performed at a speed of 300 r / min under ultrasonic oscillation conditions until the acetone is completely volatilized to obtain an inorganic + single-layer organic insulating coating powder, which is then pressed into shape; there is no step S5; the remaining steps and parameters are similar to those in Example 1.

[0173] The Al2O3 and MoS2 in the examples and comparative examples of the present invention can be obtained in a commercial manner.

[0174] Performance testing and result analysis:

[0175] A. Magnetic properties

[0176] (1) From Table 4 and Figure 5 It can be seen that the maximum quality factor Q of comparative example 1 max , Q max The corresponding frequency and quality factor at 100 MHz are significantly lower than those of Examples 1 and 2 of the present invention, which indicates that the iron-nickel alloy powder with an average particle size of >2 μm is not conducive to improving the quality factor of the magnetic powder core, especially in the high frequency band of 30 MHz-100 MHz.

[0177] (2) It can be seen from Table 4 that the saturation magnetic flux density of Comparative Example 4 is significantly lower than that of the embodiment of the present invention, which indicates that the introduction of rare earth-doped ferrite powder into the insulating coating of the magnetic powder core is beneficial to improving the saturation magnetic flux density of the magnetic powder core while ensuring a higher magnetic permeability and quality factor Q in the test frequency band.

[0178] (3) It can be seen from Table 4 that the magnetic permeability and quality factor of Comparative Examples 5 and 6 are significantly lower than those of the embodiment of the present invention, which indicates that the introduction of nano-SiO2 and Al2O3 powders into the insulating coating of the magnetic powder core is beneficial to improving the magnetic permeability and quality factor Q, especially in the high frequency band of 30MHz-100MHz, which is more conducive to the application of the magnetic powder core at high frequencies.

[0179] (4) Furthermore, compared with Comparative Examples 4 and 5, the magnetic properties of Comparative Examples 7 and 8 further slightly decreased, which indicates that the organic resin in the double-layer insulation coating and the rare earth doping have a positive effect on improving the comprehensive magnetic properties of the iron-nickel alloy magnetic powder core.

[0180] (5) From Table 4 and Figure 4-7 It can be seen that the embodiment of the present invention can obtain excellent magnetic properties through inorganic + double-layer organic insulation coating, especially at a high frequency of 30MHz to 100MHz, it has high magnetic permeability, high quality factor, higher saturation magnetic induction intensity and more stable magnetic permeability change rate. For example, in the test frequency band, most of them can achieve: magnetic permeability>22, maximum quality factor>240, frequency corresponding to the maximum quality factor>32MHz, the quality factor at 100MHz is above 39, and can even reach above 90, and the saturation magnetic induction intensity is basically above 1.30T.

[0181] (6) Further analysis shows that by controlling the particle size and addition amount of SiO2 powder (such as Examples 6-10), it is beneficial to further improve the magnetic properties, especially to better balance higher magnetic permeability and high quality factor at high frequencies; by controlling the particle size of Al2O3 powder (such as Example 14), it is beneficial to further improve the magnetic properties, especially the magnetic permeability and quality factor at high frequencies; by adding layered MoS2 to the second organic insulating coating (such as Example 15), it is beneficial to further improve the magnetic properties, especially the magnetic permeability and quality factor at high frequencies.

[0182] B. Other performance

[0183] The magnetic powder core obtained in the embodiment of the present invention has good temperature resistance and can work normally in the range of -60°C to 200°C. Such a wide temperature range makes the magnetic powder core obtained in the embodiment of the present invention suitable for various environmental conditions, including extremely low temperature and high temperature application scenarios; after pressing and molding, the density is ≥6.8g / cm 3, the higher density reflects that the magnetic powder core pressed blank obtained in the embodiment of the present invention has higher mechanical properties, and can better maintain its structural integrity and performance stability in an environment with greater vibration or impact. In addition, the mechanical properties and thermal stability of Example 5 are equivalent to those of Examples 3 and 4, and the magnetic properties are slightly improved, which shows that by controlling the mass ratio of silicone resin and epoxy resin, it is beneficial to achieve an optimal balance between magnetic properties, mechanical properties and thermal stability. Compared with Comparative Examples 4 and 5, the mechanical properties and thermal stability of Comparative Examples 7 and 8 are further slightly reduced, which shows that the organic resin in the double-layer insulation coating has a positive effect on improving the mechanical properties and thermal stability of the iron-nickel alloy magnetic powder core.

[0184] Table 3: Raw materials and their proportions of the examples and comparative examples

[0185]

[0186]

[0187]

[0188] Table 4: Performance test results of examples and comparative examples

[0189]

[0190]

[0191] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any changes or substitutions that can be easily conceived by any technician familiar with the technical field within the technical scope disclosed by the present invention should be covered within the protection scope of the present invention.

Claims

1. A method for preparing a high-frequency and high-performance iron-nickel alloy magnetic powder core, characterized in that: The following steps are involved: S1. Raw material preparation: An iron-nickel alloy powder obtained by a physical vapor condensation method is selected, wherein the average particle size D is less than 2 μm and [Fe] / [Ni] is 0.8-1.2; wherein [Fe] and [Ni] represent the mass percentages of Fe and Ni in the chemical composition of the iron-nickel alloy powder; S2. Preprocessing: The iron-nickel alloy powder is subjected to high temperature pretreatment in an oxygen-free environment; S3, blending the pretreated iron-nickel alloy powder with nano-SiO2 powder by ball milling to obtain inorganic insulating coated powder; S4, mixing an organic silicone resin, an epoxy resin, a coupling agent and a diluent to obtain a mixed resin; the mass ratio of the organic silicone resin to the epoxy resin is (1-5):1, and the diluent is a volatile solvent; A portion of the mixed resin is taken out as the first resin, and the rare earth-doped nano ferrite powder is added to the first resin to obtain a first coating agent; the inorganic insulating coating powder obtained in S3 is added to the first coating agent, and stirred until the diluent in the first coating agent is completely volatilized to obtain an inorganic + first organic insulating coating powder; S5, taking the remaining part of the mixed resin as the second resin, adding the nano-Al2O3 powder into the second resin to obtain a second coating agent; adding the inorganic + first organic insulating coating powder obtained in S4 into the second coating agent, stirring until the diluent in the second coating agent is completely volatilized, to obtain an inorganic + double-layer organic insulating coating powder; S6. Pressing and molding: Pressing and molding the inorganic + double-layer organic insulating coating powder obtained in S5 to obtain an iron-nickel alloy magnetic powder core.

2. The preparation method according to claim 1, characterized in that: Based on the mass of the iron-nickel alloy powder, in step S4, the total amount of the silicone resin and the epoxy resin added is 1-8wt%, and the amount of the coupling agent added is 0.5-3wt%.

3. The preparation method according to claim 1, characterized in that: In step S5, nano-Al2O3 powder and layered MoS2, or layered MoS2 is added to a second resin to obtain a second coating agent; the lateral size of the layered MoS2 flakes is 10-30 μm.

4. The preparation method according to claim 1, characterized in that: Based on the mass of the iron-nickel alloy powder, in step S3, the amount of the nano-SiO2 powder added is 2-6wt%; and / or, in step S4, the amount of the rare earth-doped nano-ferrite powder added is 0.5-2wt%; and / or, in step S5, the amount of the nano-Al2O3 powder added is 0.5-2wt%.

5. The preparation method according to claim 1, characterized in that: In step S4, the mass ratio of the silicone resin to the epoxy resin is (1.5-2.5):1; and / or, In step S3, the particle size of the nano-SiO2 powder is 20-70nm; and / or, in step S4, the particle size of the rare earth-doped nano-ferrite powder is 5-50nm; and / or, in step S5, the particle size of the nano-Al2O3 powder is 5-70nm.

6. The preparation method according to claim 1, characterized in that: In step S1, the coefficient of variation of the particle size distribution of the iron-nickel alloy powder, i.e., the CV value, is ≤ 25%; and / or, The iron-nickel alloy powder is spherical particles, and the sphericity δ of each spherical particle is ≥ 99.6%; and / or, The repose angle of the iron-nickel alloy powder is less than 30°.

7. The preparation method according to claim 1, characterized in that: In step S4, the ferrite powder includes at least one of manganese-zinc ferrite powder, nickel-zinc ferrite powder, cobalt-zinc ferrite powder, nickel-copper-zinc ferrite powder, and manganese ferrite powder.

8. The preparation method according to claim 1, characterized in that: In step S6, the pressure of the pressing molding is 700-900 MPa.

9. An iron-nickel alloy magnetic powder core obtained by the preparation method according to any one of claims 1 to 8.

10. Use of the iron-nickel alloy magnetic powder core as claimed in claim 9 in power electronics and magnetic components operating in the frequency range of 30 MHz to 100 MHz.

Citation Information

Patent Citations

  • Iron-nickel magnetic powder core and preparation method thereof

    CN113948264A

  • Preparation method of high-frequency high-performance metal magnetic powder core

    CN118039278A

  • Composite magnetic material and magnetic molding material, magnetic powder compression molding material, and magnetic paint using the composite magnetic material, composite dielectric material and molding material, powder compression molding material, paint, prepreg, and substrate using the composite dielectric material, and electronic part

    US20020039667A1

  • Composite soft magnetic powder, composite soft magnetic powder core, and preparation method therefor

    US20140104023A1

  • Method for producing metal soft magnetic powder core resistant to high temperature heat treatment

    WO2019029146A1

Cited By

  • Anisotropic bonded magnet and preparation method thereof

    CN120340985A

  • Anisotropic bonded magnet and method of making the same

    CN120340985B

  • High-frequency ultralow-loss iron-nickel alloy powder and preparation process thereof

    CN121571645A

  • High-frequency ultra-low-loss iron-nickel alloy powder, preparation process thereof and soft magnetic material

    CN121571645B